Prevalence and Multivariable Factors Associated With Preoperative Cognitive Impairment in Outpatient Surgery in the United States. (July 2019) - Gaulton, Timothy G.; Eckenhoff, Roderic G.; Neuman, Mark D.
Abstract : Preoperative cognitive impairment increases the risk of adverse events after surgery but its prevalence in outpatient surgery has not been defined. We aimed to determine the prevalence and multivariable factors associated with cognitive impairment in individuals who present for outpatient surgery. We used data from the Health and Retirement Study, a longitudinal panel survey of older Americans. Of 1836 participants who reported having outpatient surgery, we found that 16.1% had evidence of cognitive impairment. Significant multivariable factors associated with preoperative cognitive impairment included non-Hispanic African American race, prior stroke, preoperative functional dependence, and lower socioeconomic status and education level.